Lubricin (PRG4) reduces fouling susceptibility and improves sensitivity of carbon-based electrodes. (10th February 2020) - Russo, Matthew J.; Han, Mingyu; Quigley, Anita F.; Kapsa, Robert M.I.; Moulton, Simon E.; Doeven, Egan; Guijt, Rosanne; Silva, Saimon M.; Greene, George W.
Abstract: In order to overcome the problems of reliability and accuracy often associated with electrochemical sensing in bioassays due to electrode surface fouling, we present an innovative antifouling surface coating based on lubricin (LUB). LUB is a large glycoprotein found in the articular joints of mammals with the ability to self-assemble on surfaces of different nature, creating an antiadhesive brush layer. This work demonstrates the size selective and antiadhesive properties of LUB coatings which prevent large biomolecules from adhering onto the electrode surface while simultaneously allowing smaller electroactive species to pass through the layer unimpeded. Electrochemical and surface characterisation experiments were performed using glassy carbon (GC), carbon black SPEs (CB), and reduced graphene oxide SPEs (rGO) in order to evaluate the antifouling capabilities of LUB coatings in solutions containing bovine serum albumin (BSA) and human saliva. The LUB coatings have been shown to exhibit outstanding antiadhesive properties, size selectivity, self-assembly as well as providing excellent electrochemistry in these highly fouling solutions.